2005
DOI: 10.1016/j.ccr.2005.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal apoptosis linked to EglN3 prolyl hydroxylase and familial pheochromocytoma genes: Developmental culling and cancer

Abstract: Germline NF1, c-RET, SDH, and VHL mutations cause familial pheochromocytoma. Pheochromocytomas derive from sympathetic neuronal precursor cells. Many of these cells undergo c-Jun-dependent apoptosis during normal development as NGF becomes limiting. NF1 encodes a GAP for the NGF receptor TrkA, and NF1 mutations promote survival after NGF withdrawal. We found that pheochromocytoma-associated c-RET and VHL mutations lead to increased JunB, which blunts neuronal apoptosis after NGF withdrawal. We also found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
484
5
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 486 publications
(519 citation statements)
references
References 75 publications
26
484
5
4
Order By: Relevance
“…The amino-acid residue 161 located in the Elongin C/P53-binding domain (residues 154-164) may be a key element for the function of this domain, and mutations in this region may thus develop pheochromocytoma. [28][29][30] In this study, we used PCR-direct sequencing and UPQFM-PCR methods to detect nucleotide substitutions and deletions in VHL gene in probands clinically diagnosed with VHL disease. Up to 56.3% probands did not have the family history of VHL disease, suggesting that de novo mutations in VHL gene may be relatively common in Chinese VHL disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…The amino-acid residue 161 located in the Elongin C/P53-binding domain (residues 154-164) may be a key element for the function of this domain, and mutations in this region may thus develop pheochromocytoma. [28][29][30] In this study, we used PCR-direct sequencing and UPQFM-PCR methods to detect nucleotide substitutions and deletions in VHL gene in probands clinically diagnosed with VHL disease. Up to 56.3% probands did not have the family history of VHL disease, suggesting that de novo mutations in VHL gene may be relatively common in Chinese VHL disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…The tumour pattern of VHL patients includes central nervous system and retinal hemangioblastomas, clear cell renal cell carcinoma and phaeochromocytoma. Lee et al (2005) focused on specific VHL mutations of type 2C that can cause only phaeochromocytomas and tried to elucidate the cause for their development. Interestingly, type 2C VHL mutants can bind and target HIFa for degradation (Hoffman et al, 2001).…”
Section: Resistance To Apoptosismentioning
confidence: 99%
“…This indicates that, unlike the case of haemangioblastoma and clear cell renal cell carcinoma, mechanisms other than pseudo-hypoxia play a role in phaeochromocytoma development. Lee et al (2005) found that apoptosis in phaeochromocytoma cells is mediated by c-Jun, which activates PHD3 (EglN3). To activate c-Jun, pVHL eliminates atypical-PKC activity that induces the transcription of JunB, the upstream inhibitor of c-Jun .…”
Section: Resistance To Apoptosismentioning
confidence: 99%
“…Ectopic expression of PHD1 in colon carcinoma cells inhibited tumor growth and correlated with increased necrosis and decreased microvessel density in a mouse xenograft model (Erez et al, 2003). PHD3 was found to be downregulated in colorectal cancer cells and correlated with higher tumor grade and metastasis (Xue et al, 2010) and loss of PHD3 was associated with the development of pheochromocytomas by acting downstream of c-Jun-mediated apoptosis (Lee et al, 2005). PHD2 has been reported to induce senescence in endometrial cancer cells by regulating HIF-mediated signal transduction pathways (Kato et al, 2006).…”
Section: Introductionmentioning
confidence: 99%